Chapter One: John - Mall, Shireen (WritingThreeSixty, 2018)
Say… au revoir but not goodbye; let me whisper I love you. With joy we’ll meet again, hopefully not in sorrow. So good night my love, the heavenly birds have also promised to meet us with all the joy in the world tomorrow. [But] it was so heavenly to hold you again in my arms under that silvery moon beneath the palms in Campground Road, Rondebosch, which turned into handsome pines. 16 March 1992 John Singh